2017
DOI: 10.1016/j.jpowsour.2017.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles to organic quinone flow cells. Electrode passivation by quinone reduction in acetonitrile Li electrolytes

Abstract: Hurdles to organic quinone flow cells. Electrode passivation by quinone reduction in acetonitrile Li electrolytes. Journal of Power Sources, (2017). 350.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…In our previous research, the N,N′‐dimethylated 4,4′‐bipyridinium (MV 2+ ) showed reliable performance in AORFBs application ,. So we first synthesized the N,N′‐dimethylated dipyridinium thiazolo[5,4‐d]thiazole dichloride ( (Me 2 TTz)Cl 2 ) as shown in Scheme .…”
Section: Methodssupporting
confidence: 73%
See 4 more Smart Citations
“…In our previous research, the N,N′‐dimethylated 4,4′‐bipyridinium (MV 2+ ) showed reliable performance in AORFBs application ,. So we first synthesized the N,N′‐dimethylated dipyridinium thiazolo[5,4‐d]thiazole dichloride ( (Me 2 TTz)Cl 2 ) as shown in Scheme .…”
Section: Methodssupporting
confidence: 73%
“…As shown in Figure S8, at higher concentrations of electrolytes, that is, 0.25 m [(NPr) 2 TTz]Cl 4 and 0.5 m N Me ‐TEMPO as catholyte (equivalent to 0.5 m electrons), the AORFB (13.4 Ah L −1 and 9.65 Wh L −1 ) delivered similar rate performance and slightly lower energy efficiency (68.6 % EE at 40 mA cm −2 ) than the 0.1 m [(NPr) 2 TTz]Cl 4 and 0.2 m N Me ‐TEMPO battery. Same as the previously reported viologen‐based RFBs,,,, the [(NPr) 2 TTz]Cl 4 /N Me ‐TEMPO AORFB displayed concentration dependent long‐term cycling stability. Specifically, the 0.5 m electron RFB delivered 99.94 % capacity retention per cycle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations